9514 1404 393
Answer:
see below
Explanation:
The applicable properties of exponents are ...
(a^b)^c = a^(bc)
(a^b)(a^c) = a^(b+c)
(a^b)/(a^c) = a^(b-c)
__
![(-2^2)^(-6)/(2^(-5))^(-4)=2^(-12)/2^(20)=2^(-12-20)=\boxed{2^(-32)}\\\\2^4\cdot(2^2)^(-2)=2^(4+2(-2))=2^0=\boxed{1}\\\\(2^2)^2\cdot (2^3)^(-3)=2^(2(2)+3(-3))=2^(4-9)= \boxed{2^(-5)}\\\\(-2^(-4))^(-2)\cdot(2^2)^0=2^((-4)(-2))\cdot 1= \boxed{2^8}](https://img.qammunity.org/2022/formulas/mathematics/high-school/f73bon3rass4les22uu12jqcg2w9fflemx.png)
__
Please note that ...
![(-2^2)^(-6)=(1)/((-4)^6)=(1)/(4096)=2^(-12)](https://img.qammunity.org/2022/formulas/mathematics/high-school/m4rkccqayawlo7mia9l0ojok1q34bvjxn3.png)
That is, since the outside exponent is even, the sign is immaterial. This is also true for the other expression containing -2. The result is positive.